El juego en la enseñanza – aprendizaje de la educación inicial - Villacís Delgado, Dany (2006)
In the Peruvian education it is estimated that this climate of freedom, encourage the child's creativity not only in artistic expression, but also in solving problems, and allow developing the initiative and autonomy that allows you to do things independently and decision making to choose among several alternatives. Considering that the game is of fundamental value for all people as the alienating world in which we live, • but specifically is a right and a vital necessity for the child, a few years ago I worry about the result of continuous observations They are showing that children play less and less, both in schools and in homes and open spaces. It seems that educational institutions have lost the world of imagination by giving way only to the world of reality. The incorporation of rules and regulations, organization of time and space, programs and forms of relationship in the classroom in order to prepare children for a given society have reduced the importance of play and in many cases, spontaneity of their behavior. In early childhood education diversity of games can be used: sensory, functional, imitation, symbolic dramatic, psychomotor games, music games. The principle of freedom within the framework of early childhood education, aims to offer the child a climate of freedom that allows you to manifest spontaneously, establishing the necessary limits. Less time to play and less able to do so. And on this assertion these questions arise, what is the reason or reasons? , Small spaces and unsuitable environments, excessive limits on all that are not permitted, plastic toys, structured life increasingly artificial? and how to improve this situation and return the children at least part of their right to play? The question is not an easy, simple and definitive answer, however it is interesting to develop some points which is worth pondering. In order not to overdo explanations about the importance of play as a vehicle for building learning in kindergarten stage, we will only summarize some ideas about the game concept, the features that make the game an indispensable activity for the child development, and the contributions of the game affective engine psychosexual and social development, intellectual child. Let's start first by considering that the game is a free activity, without obligation, performed, for fun and entertainment, which is not subject to rules and that develops in an area limited1 and sometimes remote from normal means of life children participants. In addition, on them is a constant that has specific characteristics and manifestations, according to different variables that affect it such as: • The space and environment either in the school context, plazas, sidewalk, park or house, • age and number of participants, toys, materials or elements used. It is true that there are several different theories about the game and each has a part of the truth about it. What can assert in relation to those theories that define the game for its function, is that this is not only pleasant and satisfying but facilitates growth leads to establish relations group, is a form of communication and is very stimulating. Therefore, the game is always a creative experience, an experience in the space-time continuum. Even to understand the idea of ​​play is useful to think of the concentration that characterizes the play of the child: a state of near distance at a time that does not support interference and which engages the body due to the manipulation of objects and because certain types of intense interest are linked to some aspects of body excitation. And you can further expand the statement specifying many of the skills you learn and develop naturally when you have access to play in stimulating spaces and the freedom to be creative and use all the potential and personality. What skills referred then to the flexibility to adapt instantly to new roles and locations, to collaborate, to group work, to solve problems, to adapt to ever-changing environment with a great deal of creativity and imagination because in the game manifest both physical and mental activity. Considering then that through play that children learn about the environment that surrounds them, about objects, to interact with others learning to live, for all that is necessary to provide opportunities for this experience, for creative impulses, motors and sensory which are the subject of the game. But accepting the game not as a strategy to promote learning but as a voluntary, spontaneous activity, no obligations, for fun and entertainment - never didactic, with freedom of choice against playthings, free to follow paced fun , ending the game at will and even modify these objects giving other functions or invent other rules. and understanding the game, with the features mentioned, should not be made possible in schools only at the end of each day as a space time "recreation" in which children can operate at will while teachers rest afterwards of having "worked "much in the room or to fill dead time between the conclusion of an activity and the beginning of another. The game should have as much or more importance than any other activity at these ages and materialize at any time of the day as emerging interests and needs of children without forgetting that has the particular feature of his gratuity, because of its process no achievements expected determined. Is inescapable and urgent compliance with the right of children to play and with courage, enthusiasm and fantasy even in the most desolate place can be specified adequate space and proper times for the game of children to be open meaning thereby that they are not no fixed destination and also safe and predictable expectations. The child in the sensorimotor stage denotes an essentially practical intelligence. The passage of reflex behaviors voluntary behavior does not occur automatically. The responses of the environment or people close to the child a decisive influence in this process. Then, early childhood education, if you present the multiple incidence of this game in the development of children recover space and time needed to stimulate it and that concrete daily. Finally in the role of the role of the teacher in front of a group playing, you will have to be attentive and respectful but without trying to penetrate that world perceives but it does not belong except as an observer invited to participate; however, and if so will avoid coordinating the game and limited to actions as directed